Empagliflozin protects glomerular endothelial cell architecture in experimental diabetes through the VEGF‐A/caveolin‐1/PV‐1 signaling pathway. Issue 4 (23rd February 2022) - Locatelli, Monica; Zoja, Carlamaria; Conti, Sara; Cerullo, Domenico; Corna, Daniela; Rottoli, Daniela; Zanchi, Cristina; Tomasoni, Susanna; Remuzzi, Giuseppe; Benigni, Ariela
Abstract: In addition to having blood glucose‐lowering effects, inhibitors of sodium glucose cotransporter 2 (SGLT2) afford renoprotection in diabetes. We sought to investigate which components of the glomerular filtration barrier could be involved in the antiproteinuric and renoprotective effects of SGLT2 inhibition in diabetes. BTBR (black and tan, brachyuric) ob/ob mice that develop a type 2 diabetic nephropathy received a standard diet with or without empagliflozin for 10 weeks, starting at 8 weeks of age, when animals had developed albuminuria. Empagliflozin caused marked decreases in blood glucose levels and albuminuria but did not correct glomerular hyperfiltration. The protective effect of empagliflozin against albuminuria was not due to a reduction in podocyte damage as empagliflozin did not affect the larger podocyte filtration slit pore size nor the defective expression of nephrin and nestin. Empagliflozin did not reduce the thickening of the glomerular basement membrane. In BTBR ob/ob mice, the most profound abnormality seen using electron microscopy was in the endothelial aspect of the glomerular capillary, with significant loss of endothelial fenestrations. Remarkably, empagliflozin ameliorated the subverted microvascular endothelial ultrastructure. Caveolae and bridging diaphragms between adjacent endothelial fenestrae were seen in diabetic mice and associated with increased expression of caveolin‐1 and the appearance of PV‐1. These endothelial abnormalities were limited by the SGLT2 inhibitor. Although no expression of SGLT2 was found in glomerular endothelial cells, SGLT2 was expressed in the podocytes of diabetic mice. VEGF‐A, which is a known stimulus for endothelial caveolin‐1 and PV‐1, was increased in podocytes of BTBR ob/ob mice and normalized by SGLT2 inhibitor treatment. Thus, empagliflozin's protective effect on the glomerular endothelium of diabetic mice could be due to a limitation of the paracrine signaling of podocyte‐derived VEGF‐A that resulted in a reduction of the abnormal endothelial caveolin‐1 and PV‐1, with the consequent preservation of glomerular endothelial function and permeability. © 2022 The Pathological Society of Great Britain and Ireland.